Understanding the association between advanced paternal age and schizophrenia and bipolar disorder. Issue 3 (4th February 2020) - Weiser, Mark; Fenchel, Daphna; Frenkel, Or; Fruchter, Eyal; Burshtein, Shimon; Yehuda, Ariel Ben; Yoffe, Rinat; Bergman-Levi, Tal; Reichenberg, Abraham; Davidson, Michael; Sandin, Sven
Abstract: Background: Previous studies reported an association between advanced paternal age at birth and increased risk for schizophrenia and bipolar disorder. While some hypothesize that this association is caused by de-novo mutations in paternal spermatozoa, others cite factors associated with psycho-social characteristics of fathers who have children at a late age. This study aims to test these hypotheses. Methods: A historical-prospective, population-based cohort study, performed by linking the Israeli Draft Board Registry and the Israeli National Psychiatric Hospitalization Registry ( N = 916 439; 4488 with schizophrenia, 883 with bipolar disorder). Odds ratios (OR) and two-sided 95% confidence intervals (CI) were calculated by logistic regression models, using paternal age as predictor and risk for later hospitalizations for schizophrenia or bipolar disorder as outcome measure. Models were first fitted unadjusted, then adjusted for paternal age at birth of the first child. Results: In the unadjusted model, offspring of fathers aged 45 and above at birth had increased risk of schizophrenia (OR = 1.71, 95% CI 1.49–1.99) and bipolar disorder (OR = 1.63, 95% CI 1.16–2.24). However, taking into account paternal age at birth of first child, advanced paternal age was no longer associated with increased risk of schizophrenia (OR = 0.60, 95% CI 0.48–0.79) or bipolar disorder (OR = 1.03, 95% CI 0.56–1.90). Conclusions: Controlling for paternal age at birth of the first offspring, advanced paternal age does not predict increased risk for schizophrenia or bipolar disorder. These data indicate that the association between advanced paternal age and having an offspring with schizophrenia and bipolar disorder is likely due to psychos-social factors, or common genetic variation associated with delayed initial fatherhood.